The Male Flirtation in the Andolesian Poetry Ibn Al-buni as An example - Jumma, Waffa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The poems of male flirtation formed a great part in the volume of poetry . There were a lot of motivation that illuminated it’s roots , and the most important types of these motives are the psychological and artistic motives that is represented in the love of some poets for slaves and fliratating of them . Some of the poets ran after beauty and embodying it where ever it was . The social motive which contributed in pubuLarising and spreading it largely , Among different groups of Andolesian people . Ibn Al-buni was . One of the most important poet who devoted most of his poems for that purpose . Ibn Albuni " is slaves lover " as he was described by people in his time . He talked to us in his poems " The male " a bout real facts and lived events .